Alterations in the functional connectivity of thalamic subregions after basal ganglia stroke - Cheng, Qiansheng; Liu, Shoufeng; Wang, Junling; Wang, Yajing; Han, Bihui; Wang, Lichen; Jin, Song (Frontiers in Neurology, 2025)
BackgroundMotor and cognitive impairments are common symptoms of basal ganglia (BG) stroke, although the underlying neurobiological mechanisms remain unclear. Therefore, we aimed to explore the alterations in functional connectivity (FC) between thalamic subregions post-BG stroke via resting-state functional magnetic resonance imaging (rs-fMRI) measurements.MethodsThis cross-sectional study compared 40 patients with BG stroke and 35 healthy controls (HCs). Seed-based FC analysis was performed for 14 thalamic subregions. Correlations between FC changes and Fugl–Meyer Assessment (FMA)/Mini-Mental State Examination (MMSE) scores were assessed.ResultsPatients exhibited hyperconnectivity between the left thalamic subregion connected with the sensory cortex (SC_thalamus) and left precuneus (t = 3.97, pFWE = 0.041) and the right SC_thalamus–left angular gyrus (t = 4.50, pFWE = 0.032). Hypoconnectivity emerged between the left thalamic subregion connected with the prefrontal cortex (PFC_thalamus) and right supramarginal gyrus (t = −5.54, pFWE = 0.015), left thalamic subregion connected with the temporal cortex (TC_thalamus) and right postcentral gyrus (t = −4.95, pFWE = 0.022), and right thalamic subregion connected with the primary motor cortex (M1_thalamus) and right medial suprafrontal gyrus (t = −5.62, pFWE = 0.012). FC strength between the right M1_thalamus and right medial suprafrontal gyrus was positively correlated with FMA (r = 0.484, pFDR = 0.033), while left PFC_thalamus–right supramarginal connectivity predicted MMSE performance (r = 0.490, pFDR = 0.021).ConclusionBG stroke disrupts thalamocortical circuitry at subregional levels, with distinct FC patterns linking to motor/cognitive deficits. These network-level insights may guide targeted neuromodulation therapies. The identified FC alterations could serve as biomarkers for monitoring recovery and personalizing interventions to improve post-stroke rehabilitation outcomes.